Sago Business Development Strategy on Pangkaroang Bulawang, Luwu Regency - Ansri Jayanti; Yusdiman; Wahyuni; Tasrim (Yayasan Putra Adi Dharma, 2024)
Industrial development and the increasing population in Indonesia, automatically reduce agricultural land that produces rice. The consumption pattern of Indonesian people in general cannot be separated from rice as a daily staple food. This study aimed to determine whether using SWOT analysis could develop the business sago in Pangkaroang Bulawang SME. For the data collection, the researchers used interview, observation, and documentation methods, and then the researchers analyzed by using SWOT analysis. The results of this research have indicated that the SWOT analysis could develop the business sago sales in Pangkaroang Bulawang SME. The results of the research from the courtesies of SME Dusun Pangkaroang Bulawang hamlet are in the grown square, where the position is profitable for the company because it has opportunities and strengths, the next step taken is maintaining the quality of the company and retaining customers